Florida Foliage House Plant Care: ZZ Plant - Richard J. Henny; Jianjun Chen (EDIS)
ZZ plant is enjoyed for its unique appearance, its ability to grow under low light conditions, and its tolerance to drought. ZZ’s naturally glossy leaves are so shiny that the plant appears to have been polished. This 2-page fact sheet was written by R. J. Henny and J. Chen, and published by the UF Department of Environmental Horticulture, July 2013.